1990
DOI: 10.1159/000217666
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen, Its Spatial Structure and Localization of Antigenic Determinants

Abstract: The effects of temperature and pH on the spatial structure of carcinoembryonic antigen (CEA) and its various derivatives are studied by circular dichroic spectroscopy and differential UV spectroscopy. The spatial organization of the protein portion of CEA and its derivatives as revealed by spectroscopic evidence is discussed with respect to the antigenic activity of the species studied. We conclude that the protein portion of CEA consists mainly of a β-structural type. Using the various modifications of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The full analysis indicated that an average oligosaccharide chain contained 3.1 Man, 5.5 GlcNAc, 3.1 Gal and 2.7 Fuc residues. The sialic acid content per oligosaccharide chain was estimated to be 0.6 (Chandrasekaran et al, 1983;Slayter & Coligan, 1975;Hammarströ m et al, 1975;Kessler et al, 1978;Pavlenko et al, 1990). The CEA carbohydrate was therefore represented by 28 trianntenary complex-type oligosaccharide chains of composition Man3GlcNAc6Gal3Fuc3NeuNAc1, which were located at putative NXT or NXS sites in the CEA sequence (except when X = Pro).…”
Section: Preparation Of Cea For Solution Scatteringmentioning
confidence: 99%
“…The full analysis indicated that an average oligosaccharide chain contained 3.1 Man, 5.5 GlcNAc, 3.1 Gal and 2.7 Fuc residues. The sialic acid content per oligosaccharide chain was estimated to be 0.6 (Chandrasekaran et al, 1983;Slayter & Coligan, 1975;Hammarströ m et al, 1975;Kessler et al, 1978;Pavlenko et al, 1990). The CEA carbohydrate was therefore represented by 28 trianntenary complex-type oligosaccharide chains of composition Man3GlcNAc6Gal3Fuc3NeuNAc1, which were located at putative NXT or NXS sites in the CEA sequence (except when X = Pro).…”
Section: Preparation Of Cea For Solution Scatteringmentioning
confidence: 99%
“…On the other hand, assuming the cross-section of gain cavity is 0.25 cm 2 , if 1 g CEA is all deposited on the gain cavity, its thickness would be 3 cm (the density is about 1.35 × 10 3 kg/m 3 ). As the molar extinction coefficient of CEA is 1×10 5 M -1 cm -1 [52], the absorption of CEA per unit length (1 cm) is 3.3 × 10 4 cm -1 (not including optical scattering or dispersion). Based on the simulation results, the minimum thickness of CEA can be detected is 1.13×10 -10 cm, which corresponds to 0.4 ng (equivalent to 2.2 fmol).…”
Section: Sensing Mechanism and Performance Evaluationmentioning
confidence: 99%
“…In this relation, the carcino–embryonic antigen ( CEA ) [ 63 , 64 ], which does not differ in high specificity and is not revealed in the bodily fluids of a healthy human, is of great interest. Its appearance and accumulation in blood (more than 5 ng/ml) evidence the presence of almost any oncological disease in the organism, like neoplasias of the digestive tract and respiratory system or carcinoma of the breast, head, or neck [ 63 ].…”
Section: Oncofetal Antigensmentioning
confidence: 99%
“…Like all the oncofetal antigens CEA is a complicated glycoprotein, the protein part of which plays the determinative role. A study of its spatial structure showed that the carbohydrate moiety stabilizes the CEA conformation [ 64 , 65 ].…”
Section: Oncofetal Antigensmentioning
confidence: 99%